Pemikiran Pendidikan Islam Kontemporer Menurut Haji Abdul Malik Karim Amrullah (Hamka) - Muhammad Arkhanul Khamsi; Nur Asiah (Arfannur, 2021)
Islamic education does not only inclined to materialism, which solely stresses educational institutions, understanding knowledge (cognitive), and acquiring skills, therefore its function in the global period is still frequently questioned. Islamic education, on the other hand, refers to science to increase faith, understanding, religiosity, and human morality in students so that they become human beings who believe and have a noble character, which can help students fortify themselves from the negative aspects of modern technological progress in the current era of globalization. According to Haji Abdul Malik Karim Amrullah (HAMKA), the formation of a human being’s personality must begin in childhood to produce a good personality, such as becoming accustomed to being honest, daring to speak the truth, being patient with obstacles and objections, being resistant to criticism, and being firm in your stance. The purpose of this paper is to find out the method of Islamic education according to Hamka and its relevance to contemporary Islamic education. The wisdom method, advise method, discussion method, and observation method are the four approaches described by Haji Abdul Malik Karim Amrullah(HAMKA) in Islamic education. Education and teaching, according to Haji Abdul Malik Karim Amrullah(HAMKA), have different meanings but must be balanced and go hand in hand; education, he contends, is more about forming attitudes while teaching, forming attitudes is more about mastering knowledge. ABSTRAK Pendidikan islam tidak hanya cenderung kepada materialisme yang hanya mengutamakan lembaga pendidikan, pemahaman ilmu pengetahuan (kognitif) dan menguasai keahlian sehingga peran pendidikan islam di era global masih sering dipertanyakan. Padahal Pendidikan Islam merujuk kepada persoalan ilmu pengetahuan yang memiliki tujuan meningkatkan keimanan, pemahaman, religiusitas dan moralitas manusia agar para peserta didik menjadi seorang insan yang beriman dan berakhlak mulia yang pada nantinya bisa membantu para peserta didik membentengi diri dari berbagai hal negatif kemajuan teknologi modern pada era globalisasi saat ini. Hamka berpendapat budi pekerti seorang insan harus dibentuk dan ditanamkan sejak dini sehingga menghasilkan karakter yang baik seperti berani berpendapat sesuai pendiriannya, berani berkata jujur, dapat menghadapi bantahan, sabar ketika dikritik, dan teguh pendirian. Tujuan dari penulisan ini agar mengetahui metode Pendidikan Islam menurut Hamka dan relevansinya pada Pendidikan Islam kontemporer. Penulisan ini menggunakan metode studi Pustaka (kepustakaan) studi Pustaka adalah pengumpulan data melalui dokumen, artikel, dan buku sehingga menghasilkan suatu kesimpulan. Adapun 4 metode yang dijelaskan oleh Hamka dalam pendidikan islam terdiri dari: metode hikmah, metode nasihat, metode diskusi dan metode observasi. Hamka mengemukakan didalam pendidikan dan pengajaran terdapat perbedaan makna tapi harus seimbang dan beriringan, beliau mengatakan pendidikan bersifat pada pembentukan sikap sedangkan pengajaran bersifat pada ilmu pengetahuannya.